Descubrir la emergencia, disolver la revolución: el cambio científico a través de sus metáforas - Fragio, Alberto (Revista de Filosofía, 2007)
In this paper I deal with the evolution of different views concerning “scientific change”, from a metaphorological approach. Metaphors like “discovery”, “revolution”, “emergence” or dissolution” not only have had a heuristic value in relation to the production of historical narratives and philosophical theories on the dynamics of science, but also have remained inextricablely bound to different views on will undertake an analysis of T. S. Kuhn’s early works in connection with H. Blumenberg´s metaphorology, I. Hacking´s historical ontology and L. Daston´s historical epistemology. I will argue that among the main contributions of the two latter accounts we can detect a non holistic conception of scientific change.